Alternative non-Portland binders - Hanein, Theodore; Gómez-de-la-Torre, María de los Ángeles; Zhang, Zuhua; Provis, John L. (Mineralogical Society of America, 2022)
A background on non-Portland cementitious binders is presented, followed by a review of the key alternative binders that are currently of interest. The mineralogy of these cements is described, along with phases present in the reacted/hardened materials. The similarities and differences between the setting processes, as controlled by reactions at the solid– liquid interface, provide insight into the ways in which different classes of binders develop their performance and thus offer value to society.
Keywords: Cemento; Calcium Aluminate Cements; Belite Cement; Alkali-activated Materials; Magnesia Silicate Cements; Magnesia Phosphate Cements; Sorel Cements; Carbonation-hardening Cement; Calcium sulfoaluminate cement; Low-carbon binders